1972
DOI: 10.1063/1.1676945
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Rotational Zeeman Effect in Thioformaldehyde

Abstract: The high-field rotational Zeeman effect has been observed in thioformaldehyde. The magnetic susceptibility anisotropies are 2Xaa-Xbb-Xcc=S2.3± 1.1 (X 10-j! erg/G2· mole) and 2Xbb-Xaa-Xcc= -S.1± 0.7. The molecular g values with uniquely determined signs are gaa= -S.2602±0.OO68, gbb= -0.1337± 0.0004, and gcc= -0.0239±0.0004. c is the out-of-plane axis and the a axis is the dipole axis. gaa represents the largest molecular g value yet measured. Use of these five Zeeman parameters and the known structure gives the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The electronic contribution is calculated as ∆B i,el = −B i,e g ii m e /m p , where the g ii are components of the rotational g-tensor and m e and m p are the masses of the electron and the proton, respectively (Oka & Morino 1961). We took the g ii values of thioformaldehyde from the very accurate Zeeman measurements of Rock & Flygare (1972). The centrifugal distortion contribution is evaluated as ∆A cent = ∆B cent = 4 τ abab /2 and ∆C cent = −3 4 τ abab /4 (Oka & Morino 1961).…”
Section: Structural Parameters Of Thioformaldehydementioning
confidence: 99%
“…The electronic contribution is calculated as ∆B i,el = −B i,e g ii m e /m p , where the g ii are components of the rotational g-tensor and m e and m p are the masses of the electron and the proton, respectively (Oka & Morino 1961). We took the g ii values of thioformaldehyde from the very accurate Zeeman measurements of Rock & Flygare (1972). The centrifugal distortion contribution is evaluated as ∆A cent = ∆B cent = 4 τ abab /2 and ∆C cent = −3 4 τ abab /4 (Oka & Morino 1961).…”
Section: Structural Parameters Of Thioformaldehydementioning
confidence: 99%
“…We only consider experimental geometries here, taken from ref apart from ozone, for which we use r = 1.2717 Å and θ = 116.78° . With the exception of ammonia and thioformaldehyde, we compare results with the experimental g tensors compiled by Wilson et al For ammonia, we found experimental results with smaller error bars; for thioformaldehyde, we used −5.2602 for the dominant diagonal element of the g tensor, noting that Wilson et al used an incorrect value of −5.6202 because of a typographical error in the original experimental paper 1 Molecules Considered in This Study carbon monoxide [CO], carbon sulfide [CS], carbon selenide [CSe], hydrogen cyanide [HC 15 N], fluoro cyanide [FC 15 N], chloro cyanide [ClC 15 N], bromo cyanide [BrC 15 N], carbonyl sulfide [OCS, OC 34 S, O 13 CS], nitrous oxide [ 15 N 15 NO, 14 N 14 NO], carbonyl selenide [OC 80 Se, OC 76 Se], methylidene phosphine [HCP, DCP], hydrogen boron sulfide [HBS], fluoro acetylene [FCCH], chloro acetylene [ 35 ClCCH, 37 ClCCH], bromo acetylene [ 79 BrCCH, 81 BrCCH], ammonia [ 15 NH 3 ], trifluoromethane [CHF 3 ], methylisocyanide [CH 3 14 NC], acetonitrile [CH 3 C 15 N, CH 3 C 14 N, CD 3 C 14 N], fluoromethane [CH 3 F], chloromethane [CH 3 Cl], acrolein [CH 2 CHCHO], propene [CH 2 CHCH 3 ], propynal [HCCCHO], dimethyl ether [CH 3 OCH 3 ], dimethylsulfane [CH 3 SCH 3 ], acetaldehyde [CH 3 CHO], formaldehyde [H 2 CO], thioformaldehyde [H 2 CS], formic acid [HCOOH], formamide [HCONH 2 ], glycoaldehyde [CH 2 OHCHO], methyl formate [HCOOCH 3 ], ketene [H 2 CCO], difluoromethane [CH 2 F 2 ], carbonic difluoride [F 2 CO], formyl fluoride [HFCO], fluoroethene [CFHCH 2 ], 1,1-difluoroethene [CF 2 CH 2 ], cis -difluoroethene [CFHCFH], fluoroethane [CFH 2 CH 3 ], trifluoroethene [CF 2 CFH], ozone [O 3 ], sulfur dioxide [SO 2 ], difluorooxide [F 2 O], hypofluoros acid [HOF], water [H 2 O], hydrogendisulfide [H 2 S], methylenecyclopropane [C 4 H 6 ], cyclopropene [C 3 H 4 ], aziridine [C 2 H 5 N], oxirane [C 2 H 4 O], thiirane [C 2 H 4 S], cyclopropenone [C 3 H 2 O], methylcyclopropene [C 4 H 6 ], cyclobutene [C 4 H 6 ], oxetane [C 3 H 6 O], β-propiolactone [C 3 H 4 O 2 ] …”
Section: Theory and Computational Detailsmentioning
confidence: 99%
“…56 With the exception of ammonia and thioformaldehyde, we compare results with the experimental g tensors compiled by Wilson et al 30 For ammonia, we found experimental results with smaller error bars; 57 for thioformaldehyde, we used -5.2602 for the dominant diagonal element of the g tensor, noting that Wilson et al used an incorrect value of -5.6202 because of a typographical error in the original experimental paper. 58 We commenced by performing extensive investigations into the choice of the auxiliary Gaussian basis functions g t (r) for the expansion of the potential in eq 8 and the value of the filter in the singular-value decomposition (SVD) procedure used to construct the inverse Hessian in the optimization schemes. For the auxiliary basis, we considered both eventempered basis sets and the use of the primary orbital basis.…”
Section: Theory and Computational Detailsmentioning
confidence: 99%